KONCEPTUALIZIRANJE IZRAVNE DEMOKRACIJE KAO SJECIŠTA RAZLIČITIH OBLIKA PREDSTAVLJANJA - Miloš, Matija (Pravni zapisi, 2020)
As an exceptional device in the life of contemporary constitutional democracies, direct democracy is normally considered to be separate from representation. In this paper, I explore this well-established divide, asking how it interacts with our understanding of the central subject of direct democracy, the people. I show how theorizing that takes its cue from the dichotomy between “absence” and “presence”, ascribed to the separation of representation and forms of direct democracy, is tied with identifying the active electorate and the people. On the other hand, this approach is inept for comprehending the ways representations of the people are produced and instrumentalized in the wake of direct democracy. In this paper, I suggest that this phenomenon may be approached by examining how direct democracy is entangled with representing “the people” through arguments, processes and constructs.